Developing Self-regulation of Learning and Teaching Skills Among Teacher Candidates - Bembenutty, Héfer. author. aut Link
XVII, 134 p. 14 illus.
Keywords: This book reports an in-depth case study and the student teaching experience of four preservice teachers during practical and clinical experiences in classroom in an urban community in New York. It examines the associations between preservice teachers’ self-regulatory skills and motivational beliefs and their clinical experience both in the college training classroom and in the school settings. The experiences of the students are examined from the perspective of social cognitive theory and self-regulation theory. The authors present a concise summary of an in-depth case study with practical applications across a wide spectrum of fields. They also summarize and give an overview of theories, issues, core concepts related to the self-regulatory experience and motivation of the four case studies. In an effective blend of theory and case histories, Bembenutty, White, and Vélez provide valuable information and advice for prospective teachers and teacher educators. Their focus on help seeking is critical given the array of resources available to overcome early difficulties especially for teachers with significant challenges. Also important is helping them understand the role of delay of gratification in the face of expanding sources of distraction. Stuart A. Karabenick, Research Professor, University of Michigan This book builds a really strong case for the importance of self-regulation in teacher education. Moreover, it tells a fascinating story of educational success against the odds, made possible by personal stamina as well as contextual support. Both teacher students and teacher educators around the world will find this book a wonderful inspiration. Ivar Bråten, Professor, University of Oslo, Norway This is a practical book which provides a compelling narrative with page after page on teacher self-regulatory functioning. I recommend this book for teacher preparation programs, and I will definitely share itwith many of my students and colleagues. Anastasia Kitsantas, Professor, George Mason University .